Analysis of Mother's Day Celebration via circular statistics. - Abuzaid, Ali H. (2012)
This paper, handles with much emphasis, Mother's Day celebration around the world - a day that is celebrated on various days in different countries. These days are marked in relation to certain historical, religious or mythical events for every nation.

The celebration of mother's day by 152 nations is analyzed using a set of circular statistics procedures to study its characteristics. The frequencies of celebration days are modeled, possible clusters and outliers are defined to assess possible factors that may affect the celebration in a certain date. These factors are found to be culture, language, colonization and neighborhood with insignificant role of religion.
Keywords: Special days; Mother's Day; Sampling (Statistics); Outliers (Statistics); Cluster analysis